Pendampingan Guru Matematika dan Siswa SDN 05 Wagirkidul dan Dalam Meningkatkan Minat Belajar Berhitung Peserta Didik Melalui Metode Jarimatika - Siti Nur'aini; Fuad Fitriawan (Social Science Academic, 2025)
This research is motivated by the potential of Wagirkidul Village's existing human resources in the education sector, where it is known that Wagirkidul has many educational institutions which of course the implementation of learning must be considered in order to support the success of the vision and mission of the institution, including success in learning mathematics. Because of this, the author is interested in providing service assistance to mathematics teachers at SDN 05 Wagirkidul in learning mathematics through the Jarimatika method, where the purpose of this service is to: 1) provide basic knowledge about mathematical arithmetic operations with fingers. 2) produce good modules for educators which can then be used in teaching and learning in the classroom. The method used is the method of lectures, practice, question and answer, discussion and exercises using the prepared grammar modules. The results of the data show that the ability to count has increased after using the jarimatics method, this can be seen from the results of tests on students by teachers who take part in the assistance of the jarimatics method, which are in the medium category. The numeracy skills of students who learn using the jarimatics method are better than children who learn using the usual method. So it can be concluded that the jarimatics method can make the learning process more fun and increase children's interest in learning to count.